Pre-Departure Training and Personal Resources: How it Affects Acculturative Stress? - Widayanti Widayanti; Dina Sartika (ETIKONOMI, 2020)
One of the efforts made by the government to reduce the unemployment rate in Indonesia is by conducting an overseas apprenticeship program. As an international assignment, this apprenticeship program leads to social problems such as stress. This research seeks to examine and analyze the influence of pre-departure training on acculturative stress with personal resources as a moderating variable. The respondents of this study were 215 migrant workers from West Java. This research used process analysis to analyze data. The result shows that there is a negative influence of pre-departure training on acculturative stress. Besides that, personal resources strengthen the influence of pre-departure training on acculturative stress. The higher a level of personal resources possessed, the more it will strengthen the influence of pre-departure training on acculturative stress. These findings support the statement that personal resources are one of the leading indicators that affect an individual's performance at work.JEL Classification: M53, J61How to Cite:Widayanti., & Sartika, D. (2020). Pre-Departure Training and Personal Resources: How it Affects Acculturative Stress?. Etikonomi: Jurnal Ekonomi, 19(1), 31 – 40. https://doi.org/10.15408/etk.v19i1.11884.